A next-generation liquid xenon observatory for dark matter and neutrino physics. (1st January 2023) - Aalbers, J; AbdusSalam, S S; Abe, K; Aerne, V; Agostini, F; Ahmed Maouloud, S; Akerib, D S; Akimov, D Y; Akshat, J; Al Musalhi, A K; Alder, F; Alsum, S K; et al.
Abstract: The nature of dark matter and properties of neutrinos are among the most pressing issues in contemporary particle physics. The dual-phase xenon time-projection chamber is the leading technology to cover the available parameter space for weakly interacting massive particles, while featuring extensive sensitivity to many alternative dark matter candidates. These detectors can also study neutrinos through neutrinoless double-beta decay and through a variety of astrophysical sources. A next-generation xenon-based detector will therefore be a true multi-purpose observatory to significantly advance particle physics, nuclear physics, astrophysics, solar physics, and cosmology. This review article presents the science cases for such a detector.